Konsep Manajemen Kebutuhan Transportasi (MKT) Sebagai Alternatif Pemecah Masalah Transportasi Perkotaan di DKI Jakarta - Ofyar Z Tamin (The Institute for Research and Community Services, Institut Teknologi Bandung, 1999)
The monetary crisis which occurs in our country very recently affected that the conventional approach for solving the urban transportation problem in DKI Jakarta can no longer be used for the near future. The paper will discuss in detail the Transport Demand Management concept, which is hoped to replace the conventional approach to solve the urban transportation problem in DKI Jakarta.